Anglo-Dutch premium auctions in eighteenth-century Amsterdam - Christiaan van Bochove; Lars Boerner; Daniel Quint (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2012)
This paper studies Anglo-Dutch premium auctions used in the secondary market for financial securities in eighteenth-century Amsterdam, Europe's financial capital at the time. An Anglo-Dutch premium auction consists of an English auction followed by a Dutch auction, with a cash premium paid to the winner of the first round regardless of the second-round outcome. To rationalize the introduction and continued use of this auction format, we need to determine whether bidding behavior was consistent with equilibrium play. We model this auction format theoretically, and show that the likelihood of a bid in the second round should be higher when there is greater uncertainty about the value of the security being sold. We then test this prediction on data from 16,854 securities sold at auction on 469 days over an 18-year period in the late 1700s; using several different proxies for the uncertainty of a given security's value, we find support for this theoretical prediction.
Keywords: D44; N23; 330; Auktionstheorie; Finanzmarkt; Sekundärmarkt; Geschichte; Amsterdam